Cast into the deep : shaping the Filipino moral imagination for social change - Belita, Jimmy A. ([Congregation of the Mission] : [Tandang Sora Avenue], 1994)
This book provides with a sober and brilliant analysis of the 'hard facts' of Philippine life and why we should consider the local culture in teaching moral values.
PART 1. The ole of imagination in moral education -- PART 2. Shaping Filipino moral imagination.
Includes bibliographical references and index.
Keywords: MORAL EDUCATION -- PHILIPPINES